Implementasi Sistem Manajemen Keselamatan dan Kesehatan Kerja (SMK3) Pada Pekerjaan Proyek Pembangunan Infrastruktur - I Komang Alit Astrawan Putra; I Gusti Bagus Angga Surya Dharma (Jurnal Ilmiah Kurva Teknik, 2023)
ABSTRACT: The development of technology and information today is very closely related to capacity building in the world of construction, especially in the implementation of infrastructure development projects. This development can be seen from the use of various modern equipment, types of materials and production methods and procurement processes. Humans as workers also experience development in their efforts to get jobs armed with skills and expertise. Based on this, workers as the spearhead in the management and implementation of the project are the main concern to ensure the safety and health of their work In this study it is devoted to knowing the general conditions of the contractor's activities and work activities in carrying out the Occupational Safety and Health Management System, how the Occupational Safety and Health Management System (SMK3) is owned by the contractor, both in field conditions or standard operating conditions and how conformity elements of the implementation of the Occupational Health and Safety Management System with ISO 45001:201, Government Regulation Number 50 of 2012. From the research results it can be said that contractors engaged in road construction construction services, in carrying out their projects in accordance with their duties, principals and functions and produce various types of construction products, such as "U-ditch" pre-cast products. Implementation In implementing project SMK3, planning management is determined using SMKK (Construction Safety Management System) which refers to PUPR Ministerial Regulation Number 10 of 2021. In implementing OSH performance, companies have made efforts to carry out SMK3 procedures in general that are appropriate and refer to PP Number 50 of 2012 and ISO 45001: 2018 with the results of an analysis of the implementation for the K3 performance aspect which refers to the two SMK3 elements according to Government Regulation Number 50 of 2012 and ISO 45001: 2018 of 74.8% and for the provision of various safety support facilities at work of 71% .